Expression of the Central Obesity and Type 2 Diabetes Mellitus Genes is Associated with Insulin Resistance in Young Obese Children - Skoczen, S.; Wojcik, M.; Fijorek, K.; Siedlar, M.; Starzyk, J. B. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Objectives: The assessment of the health consequences associated with obesity in young children is challenging. The aims of this study were: (1) to compare insulin resistance indices derived from OGTT in obese patients and healthy control (2) to analyze central obesity and Type 2 Diabetes genes expression in obese children, with special attention to the youngest group (< 10 years old).Patients and methods: The study included 49 children with obesity (median age 13.5 years old), and 25 healthy peers. Biochemical blood tests and expression of 11 central obesity and 33 Type 2 Diabetes genes was assessed.Results: A significant difference in insulin resistance between obese and non-obese adolescents was observed in all studied indices (mean values of the insulin levels: 24.9 vs. 9.71 mIU/L in T0, 128 vs. 54.7 mIU/L in T60 and 98.7 vs. 41.1 mIU/L in T120 respectively; AUC: 217 vs. 77.2 ng/ml*h, mean values of B% (state beta cell function), S% (insulin sensitivity), and IR were 255 (±97) vs. 135 (±37.8), 46.6 (±37.3) vs. 84.2 (±29.6) and 3 (±1.55) vs. 1.36 (±0,56); HIS, WBIS and ISIBel median 3.89, 44.7, 0.73 vs. 8.57, 110, 2.25. All comparisons differed significantly p<0.001). Moreover, insulin sensitivity was significantly better in the older obese group (>10 years old): median AUC 239 vs. 104 ng/ml*h, and HIS, WBIS and ISIBel 3.57, 38, 0.67 vs. 6.23, 75.6, 1.87 respectively in the obese older compared to the obese younger subgroup, p<0.05. The expression of 64% of the central obesity genes and 70% of Type 2 Diabetes genes was higher in the obese compared to control groups. The differences were more pronounced in the younger obese group.Conclusion: Insulin resistance may develop in early stage of childhood obesity and in very young children may be associated with higher expression of the central obesity and Type 2 Diabetes genes.
Keywords: microarrays; metabolic syndrome; adolescents